Barium-titanium-based ferroelectric thick film and preparation method thereof

Through the preparation method of barium-titanium-based ferroelectric thick film, the problem of insufficient mechanical strength and durability of traditional ferroelectric thin film devices is solved, and a high density and large thickness ferroelectric film is achieved, which reduces the preparation cost and increases the application potential.

CN119744116AActive Publication Date: 2025-04-01TONGJI UNIV
12 Cites 0 Cited by

Patent Information

Application Number
CN202411911439.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Traditional ferroelectric thin film devices have problems such as poor mechanical strength and durability and weak integration capabilities. The thickness of thick films prepared by the sol-gel method is usually less than 100μm, with low density, low dielectric performance and increased leakage current, which is not conducive to promotion and application.

Method used

The preparation method of barium-titanium-based ferroelectric thick film is adopted, including preparation of composite precursor solution sol, chemical treatment for preventing cracking and inhibiting hydrolysis, 99.99% platinum base texture adaptive dilute sol three-dimensional mesh adhesion layer, drip-coated thick sol filled viscous bonding layer, secondary sintering molded composite thick film structure, and annealing treatment shaped composite thick film.

Benefits of technology

The high density and large thickness of the barium-titanium-based ferroelectric thick film are achieved, which solves the problems of cracking and uneven coating on the surface of the film, reduces the preparation cost, improves the mechanical strength and durability of the film, and enhances its application potential in the field of energy storage and conversion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119744116A_ABST
    Figure CN119744116A_ABST
Patent Text Reader

Abstract

The invention relates to a barium-titanium-based ferroelectric thick film and a preparation method thereof, and the preparation method comprises the steps: 1) preparing a barium precursor dilute and concentrated solution and a titanium precursor dilute and concentrated solution, mixing, stirring and aging the barium precursor dilute solution and the titanium precursor dilute solution to obtain dilute gel, and mixing, stirring and aging the barium precursor concentrated solution and the titanium precursor concentrated solution to obtain concentrated gel; (2) spin-coating a substrate with dilute gel for multiple times, drying and heating after spin-coating each time to obtain a dilute sol three-dimensional net-shaped adhesion layer, and sintering to obtain a first-stage substrate; (3) spin-coating the first-stage substrate with the thick gel for multiple times, drying and heating after spin-coating each time, so as to obtain a thick sol filled viscous fitting layer, and sintering, so as to obtain a second-stage substrate; and 4) annealing the second-stage substrate to obtain the barium-titanium-based ferroelectric thick film. Compared with the prior art, the thickness of the obtained ferroelectric film is 150-250 [mu] m, and compared with other ferroelectric films with poor density at present, the ferroelectric film has good thickness, which means that a larger ferroelectric effect may be generated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of film material preparation, and relates to a barium-titanium-based ferroelectric thick film and a preparation method thereof. Background Art

[0002] Ferroelectric thin film devices have become a hot topic in the field of device preparation due to their wide applications in energy storage and conversion, non-volatile memory, and micro-nano devices. However, traditional thin film devices have problems such as poor mechanical strength and durability, and weak integration capabilities. As an alternative to ferroelectric thin film devices, preparing large-sized ferroelectric thick films through specific processes has become an effective way to solve the problem of thin film shortage.

[0003] Among the many methods for preparing membrane devices, the sol-gel method, as a preparation method based on the principle of chemical reaction, can accurately control the size and morphology of ions and reduce the particle size of the coating material in the device. At the same time, the gel prepared by the sol-gel method must be repeatedly heat-treated during the heating process, which significantly reduces the gaps on the surface of the membrane device and obtains a ferroelectric film with a uniform surface during thermal cycling and secondary sintering. However, most membrane devices using this method are usually less than 100μm thick, have many holes, low density, low dielectric properties, and increased leakage current, which is not conducive to promotion and application.

[0004] At present, in the research on preparing thick films based on the sol-gel method, most of them use multi-layer metal-oxide-silicon substrates, such as Pt (100nm) / Ti (30nm) / SiO2 (500nm) / Si (500mm) silicon wafer substrates. The substrates prepared based on this type of micro-nano film processing are expensive and the electrode preparation is difficult, which limits its application range. Therefore, it is urgent to find a preparation method for pure metal substrate lead-free ferroelectric thick films that can increase the thickness of the thick film and have a low preparation cost. Summary of the invention

[0005] The purpose of the present invention is to provide a barium-titanium-based ferroelectric thick film and a preparation method thereof, which are used to solve the problems of film surface cracking, uneven coating and insufficient thickness in traditional preparation methods.

[0006] The preparation method provided by the present invention mainly includes: preparation of composite precursor solution sol, anti-cracking and hydrolysis inhibition chemical treatment, 99.99% platinum substrate texture adaptive dilute sol three-dimensional mesh adhesion layer, dripping thick sol filling viscous bonding layer, secondary sintering to form a composite thick film structure, and annealing treatment to shape the composite thick film.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] The first aspect of the present invention provides a method for preparing a barium-titanium-based ferroelectric thick film, the method comprising the following steps:

[0009] 1) preparing a barium precursor dilute solution and a barium precursor concentrated solution containing a barium source and a hydrolysis inhibitor, a titanium precursor dilute solution and a titanium precursor concentrated solution containing a titanium source and a hydrolysis inhibitor, mixing the barium precursor dilute solution and the titanium precursor dilute solution, adding an anti-cracking agent and aging to obtain a composite precursor dilute gel, mixing the barium precursor concentrated solution and the titanium precursor concentrated solution, adding an anti-cracking solvent and aging to obtain a composite precursor concentrated gel;

[0010] 2) Spin coating the composite precursor dilute gel on the substrate for multiple times, and drying and heating after each spin coating to obtain a dilute sol three-dimensional network adhesion layer, and sintering it once to obtain a first-stage substrate;

[0011] 3) Spin coating the thick gel on the first-stage substrate in step 2) for multiple times, and drying and heating after each spin coating to obtain a thick sol-filled viscous bonding layer, and sintering it twice to obtain a second-stage substrate;

[0012] 4) Annealing the second stage substrate in step 3) to obtain a barium-titanium based ferroelectric thick film.

[0013] Furthermore, in step 1), in the dilute barium precursor solution, the feed ratio of the barium source, the solvent and the hydrolysis inhibitor is (5-6) g: (20-30) mL: (6-8) mL, and in the concentrated barium precursor solution, the feed ratio of the barium source, the solvent and the hydrolysis inhibitor is (5-6) g: (18-24) mL: (6-8) mL;

[0014] In the titanium precursor dilute solution, the feed ratio of the titanium source, the solvent and the hydrolysis inhibitor is (5-7) mL: (25-35) mL: (6-8) mL, and in the titanium precursor concentrated solution, the feed ratio of the titanium source, the solvent and the hydrolysis inhibitor is (5-7) mL: (20-28) mL: (6-8) mL;

[0015] The volume ratio of the dilute barium precursor solution or the concentrated barium precursor solution to the anti-cracking agent is 1:(0.17-0.2);

[0016] In the composite precursor dilute gel and composite precursor concentrated gel, the molar ratio of barium element to titanium element is 1:(1-2).

[0017] Further preferably, in the titanium precursor dilute solution, the feed ratio of the titanium source, the solvent and the hydrolysis inhibitor is 5.11 g:25 mL:7 mL; in the barium precursor concentrated solution, the feed ratio of the barium source, the solvent and the hydrolysis inhibitor is 5.11 g:20 mL:7 mL.

[0018] Further preferably, in the dilute titanium precursor solution, the feed ratio of the titanium source, the solvent and the hydrolysis inhibitor is 6.81 mL: 30 mL: 7 mL; in the concentrated titanium precursor solution, the feed ratio of the titanium source, the solvent and the hydrolysis inhibitor is 6.81 mL: 25 mL: 7 mL.

[0019] In order to prevent hydrolysis, it is necessary to add complexing agents or high molecular compounds and other hydrolysis inhibitors. In order to prevent cracking when preparing thick films, it is necessary to add anti-cracking solvents such as soluble polymerizers or colloid stabilizers.

[0020] Furthermore, the preparation method of the dilute barium precursor solution or the concentrated barium precursor solution is: mixing a barium source and a solvent, stirring once and twice, and then adding a hydrolysis inhibitor to obtain a dilute barium precursor solution or a concentrated barium precursor solution;

[0021] During the first stirring, the stirring temperature is 55-65°C, and during the second stirring, the stirring temperature is 75-85°C.

[0022] Furthermore, the barium source is Ba(CH3COO)2, and the titanium source is C 16 H 36 O4Ti, the solvent is CH3COOH.

[0023] Furthermore, in step 1), the hydrolysis inhibitor is selected from any one of ethylene glycol monoethyl ether, ethylenediaminetetraacetic acid or citric acid; the anti-cracking agent is selected from any one of acetylacetone, ethylene carbonate or polyol; during the stirring, the stirring temperature is 75-85°C; during the aging, the aging temperature is 26-30°C, and the aging time is 24-36h.

[0024] Furthermore, in step 2), the substrate is a platinum substrate or an aluminum substrate.

[0025] Furthermore, in step 2), the substrate is a pure metal substrate.

[0026] Furthermore, in step 2), the prepared composite precursor dilute gel is spin-coated on a 99.99% platinum substrate to texture a three-dimensional mesh adhesion layer of a certain thickness, and then, the solvent is evaporated and residual organic matter is removed by a thermal cycle treatment, i.e., a cyclic drying and heating operation. Then, a sintering is performed to eliminate the internal stress of the film to reduce cracking and deformation of the film and promote the initial formation of the crystalline phase.

[0027] Furthermore, in step 2), in the spin coating of the composite precursor dilute gel, the number of spin coating is 5-6 times, the spin coating speed is 4000-5000RPM, and the spin coating time is 30s; in the drying treatment, the drying temperature is 110-130°C, the drying time is 2-4min, and the drying atmosphere is air or oxygen; in the heating treatment, the heating temperature is 380-410°C, the heating time is 1-2min, and the heating atmosphere is air or oxygen; in the primary sintering, the sintering temperature is 790-810°C, the sintering time is 55-70min, and the sintering atmosphere is air or oxygen.

[0028] Furthermore, in step 3), the thick gel is dripped onto the first-stage substrate, and a certain thickness of the viscous bonding layer is filled on the basis of the three-dimensional mesh adhesion layer. The method of combining the adaptive composite mesh layered structure and the viscous filler is adopted to ensure that the contact angle between the bonding interface and the coating and the dripping pressure are in the optimal state of dynamic pressure control, which greatly improves the density of the thick film. Similarly, after the thermal cycle treatment (drying treatment and heating treatment), secondary sintering is performed to further promote the formation of the crystalline phase. Finally, the annealing operation is performed to promote grain growth and improve crystallinity.

[0029] Furthermore, in step 3), in the spin coating of the thick gel, the number of spin coating times is 5-6 times, the spin coating speed is 4000-5000RPM, and the spin coating time is 30s; in the drying treatment, the drying temperature is 110-130°C, the drying time is 2-4min, and the drying atmosphere is air or oxygen; in the heating treatment, the heating temperature is 380-410°C, the heating time is 1-2min, and the heating atmosphere is air or oxygen; in the secondary sintering, the sintering temperature is 790-810°C, the sintering time is 55-70min, and the sintering atmosphere is air or oxygen.

[0030] Furthermore, the spin coating acceleration is 1000 RPM / s. Too low a rotation speed will result in the prepared gel not being able to completely and evenly cover the substrate surface, while too high a rotation speed will result in the gel on the substrate surface splashing and leaving too little residual gel.

[0031] Furthermore, in step 2) and step 3), spin coating is performed on a spin coater, and drying is performed on a magnetic rotary heating table; heating treatment, primary sintering and secondary sintering are performed in a muffle furnace.

[0032] Furthermore, in step 4), in the annealing treatment, the annealing temperature is 950-1100° C., the annealing time is 290-310 min, and the annealing atmosphere is air or oxygen.

[0033] Furthermore, in step 2), the thickness of the dilute sol three-dimensional network adhesion layer is 100-200 μm; in step 3), the thickness of the thick sol-filled viscous bonding layer is 200-300 μm; in step 4), the thickness of the barium-titanium-based ferroelectric thick film is 150-250 μm.

[0034] A second aspect of the present invention provides a barium-titanium-based ferroelectric thick film, which is made by the above-mentioned preparation method.

[0035] Furthermore, the thickness of the barium-titanium-based ferroelectric thick film is 150-250 μm.

[0036] The preparation method of the present invention is divided into two stages, including mixing of core reactants, crack-proof solvents, and hydrolysis-inhibiting solvents in two stages, aging, spin coating, drying, heating, sintering, and final annealing. A composite precursor solution sol is required to be prepared, and composite precursor dilute gel and thick gel are prepared according to different ratios, that is, metal alkoxide or inorganic salt is dissolved in a solvent as a precursor to undergo polycondensation reaction, and the reaction product is aggregated into several nanometer-scale particles to form a sol, which is then aged to form a gel.

[0037] Compared with the prior art, the present invention has the following characteristics:

[0038] 1) The ferroelectric film obtained by the present invention has a thickness of 150-250 μm, which is better than other ferroelectric films with poor density, which means that a greater ferroelectric effect may be produced. The thickness of the film is doubled by secondary sintering, and the surface of the prepared film is made dense, which can solve the problem of being unable to coat a large area due to cracks on the film surface;

[0039] 2) The ferroelectric thick film obtained by using pure metal (platinum or aluminum, etc.) as the substrate in the present invention has lower cost, simpler process and better thermal conductivity than the existing substrate applicable to phase change ferroelectrics. In addition, the metal plating on the currently used silicon wafer substrate can only be processed into a planar structure due to the material limitation of the material itself, which means that the thick film has greater application potential than the existing thin film;

[0040] 3) In the film preparation process adopted by the present invention, the equipment required mainly includes a muffle furnace, a balance, a magnetic rotary heating table, a spin coater, a pyroelectric energy conversion experimental platform, etc., and no expensive equipment is required. In addition, the required raw materials are also easy to purchase, so the cost of making the film is low;

[0041] 4) The thick film device prepared by the present invention has good flexibility. When subjected to external force, the thick film material can bend, fold, twist, and other deformations without breaking, and has a high practical prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1It is a flow chart of the method for preparing the pure metal substrate lead-free ferroelectric thick film in the present invention;

[0043] Figure 2 It is a schematic diagram of the method for preparing a lead-free ferroelectric thick film on a pure metal substrate in the present invention;

[0044] Figure 3 It is a schematic diagram of the textured adaptive dilute sol mesh attachment layer and the drip-coated thick sol filling bonding layer in the present invention;

[0045] Figure 4 is the XRD diffraction pattern of the BaTi2O5 ferroelectric thick film prepared in Example 1;

[0046] Figure 5 is a scanning electron microscope image of the BaTi2O5 ferroelectric thick film prepared in Example 1;

[0047] Figure 6 This is a scanning electron microscope image of the edge of the BaTi2O5 ferroelectric thick film prepared in Example 1;

[0048] Figure 7 The piezoelectric force microscope hysteresis loop spectrum of the BaTi2O5 ferroelectric thick film prepared in Example 1;

[0049] Figure 8 is the XRD diffraction pattern of the BaTiO3 ferroelectric thick film prepared in Example 2;

[0050] Fig. 9 This is a scanning electron microscope image of the edge of the BaTiO3 ferroelectric thick film prepared in Example 2;

[0051] Fig.10 This is the piezoelectric force microscope hysteresis loop spectrum of the BaTiO3 ferroelectric thick film prepared in Example 2. DETAILED DESCRIPTION

[0052] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0053] In the following examples, unless otherwise specified, raw materials, reagents or processing techniques are all conventional commercial products or conventional processing techniques in the art.

[0054] In the following examples, a barium-titanium-based ferroelectric thick film was prepared, such as Figure 1As shown, it is a flow chart of the preparation method of pure metal substrate lead-free ferroelectric thick film, including preparation of composite precursor solution sol, anti-cracking and hydrolysis inhibition chemical treatment, texture adaptive dilute sol mesh adhesion layer, drip coating thick sol filling bonding layer, secondary sintering composite thick film structure, annealing treatment to shape the composite thick film to obtain the final thick film product; Figure 2 It is a schematic diagram of the preparation method of pure metal substrate lead-free ferroelectric thick film in the present invention, and high-quality BaTi2O5 ferroelectric thick film and BaTiO3 ferroelectric thick film are obtained by texturing an adaptive dilute sol three-dimensional network adhesion layer on a 99.99% platinum substrate, dripping a thick sol to fill a viscous bonding layer, and secondary sintering to form a composite thick film structure.

[0055] The following are more detailed implementation cases, which further illustrate the technical solutions of the present invention and the technical effects that can be obtained.

[0056] Embodiment 1:

[0057] A barium-titanium-based ferroelectric thick film——BaTi2O5 ferroelectric thick film

[0058] The preparation method thereof comprises:

[0059] (I) Preparation of composite precursor dilute gel and composite precursor concentrated gel:

[0060] The preparation method of the composite precursor dilute gel is as follows: Ba(CH3COO)2 (99.99%), C 16 H 36 O4Ti (> = 97.00%) and CH3COOH (> 99.50%) raw materials, Ba(CH3COO)2 and CH3COOH were mixed in a ratio of about 1:5, 5.11g of Ba(CH3COO)2 was added to 25mL of CH3COOH and stirred at 60°C until the solution was clear, and then stirred twice at 80°C to completely dissolve Ba(CH3COO)2. After cooling to room temperature, 7mL of ethylene glycol monoethyl ether (C4H 10 O2) to prepare a dilute barium precursor solution. 16 H 36 O4Ti and CH3COOH were mixed in a ratio of about 1:5, and 6.81 mL of C 16 H 36 O4Ti was added to 30.00 mL of CH3COOH, and then 7 mL of C4H 10O2, forming a dilute titanium precursor solution. After obtaining the two dilute precursor solutions, the dilute barium precursor solution and the dilute titanium precursor solution are mixed at a molar ratio of Ba:Ti=1:2 and continuously stirred at 80°C to obtain a transparent and uniform composite precursor solution. Subsequently, 6mL of acetylacetone is added to the composite precursor solution to control the viscosity and prevent the film from rupturing. Then, after aging at 28°C for 24-36 hours, a composite precursor dilute gel is formed.

[0061] The difference between the preparation method of the composite precursor concentrated gel and the preparation method of the composite precursor dilute gel is that Ba(CH3COO)2 and CH3COOH are mixed in a ratio of about 1:4. Specifically, 5.11 g of Ba(CH3COO)2 is added to 20 mL of CH3COOH and stirred once at 60°C until the solution is clear, and then stirred twice at 80°C to completely dissolve Ba(CH3COO)2. After cooling to room temperature, 7 mL of ethylene glycol monoethyl ether (C4H 10 O2) to prepare a dilute barium precursor solution. 16 H 36 O4Ti and CH3COOH were mixed in a ratio of about 1:4, and 6.81 mL of C 16 H 36 O4Ti was added to 25.00 mL of CH3COOH, and then 7 mL of C4H 10 O2, forming a dilute titanium precursor solution. 16 H 36 O4Ti and CH3COOH are mixed in a ratio of 1:4, and the amount of the corresponding substances added is changed accordingly. The remaining steps are the same as the above-mentioned composite precursor dilute gel preparation method.

[0062] (ii) Texture-adaptive dilute sol three-dimensional mesh adhesion layer

[0063] Figure 3Schematic diagram of texture adaptive dilute sol mesh attachment layer and drip-coated thick sol filling bonding layer. The composite precursor dilute gel prepared in step (a) is dripped on the 99.99% platinum substrate adsorbed by the spin coater, and the spin coating speed is set to 4000 to 5000RPM, the acceleration is 1000RPM / s, and the spin coating time is 30s. The gel film is deposited by spin coating. The gel spin coating operation is specifically as follows: after taking an appropriate amount of dilute gel with a dropper, it is dripped on the center of the substrate to allow it to slowly spread until the substrate is completely covered, and then the spin coater is started to obtain a layer of film after spin coating. After that, each layer of the film is subjected to thermal cycle treatment, that is, a cyclic drying and heating operation is performed to evaporate the solvent and remove residual organic matter, specifically: placed on a magnetic rotating heating table and dried at 120°C in an air atmosphere for 3 minutes to evaporate the solvent, and then placed in a muffle furnace and heated to 400°C for 2 minutes. The heating atmosphere is air to remove residual organic matter. Repeat the above gel spin coating, drying, and heating treatment steps 5-6 times to obtain the first stage 5-6 layers of film. At this time, a dilute sol three-dimensional mesh attachment layer with adaptive surface texture is formed on a 99.99% platinum substrate by dilute sol, and the thickness of the dilute sol three-dimensional mesh attachment layer is 140μm. Subsequently, it is placed in a muffle furnace and sintered at 800℃ for 1 hour to initially form a crystalline phase, thereby obtaining the first stage preliminary product, which is recorded as the first stage substrate.

[0064] (III) Drip coating of thick sol to fill the viscous bonding layer

[0065] The composite precursor concentrated gel prepared in step (a) is dropped onto the first-stage substrate obtained in step (b), and the spin coating speed is set to 4000 to 5000RPM, the acceleration is 1000RPM / s, and the spin coating time is 30s. The gel spin coating operation in step (b) is repeated, and the thick gel is spin coated on the first-stage substrate 5-6 times. After each spin coating, the film is placed on a magnetic rotating heating table and dried at 120°C for 3 minutes, and then placed in a muffle furnace and heated to 400°C for 2 minutes. At this time, a thick sol-filled viscous bonding layer is formed, and the thickness of the thick sol-filled viscous bonding layer is 240μm. After that, a secondary sintering operation is performed to form a composite thick film structure and further promote the formation of a crystalline phase. It is placed in a muffle furnace and sintered for 1 hour at 800°C to obtain a preliminary finished product of the second stage, which is recorded as the second-stage substrate.

[0066] (IV) Annealing treatment

[0067] The second-stage substrate obtained in step (iii) was annealed at 1000° C. in an air atmosphere for 5 hours to obtain a BaTi2O5 ferroelectric thick film having a thickness of 152 μm. The thickness of the obtained BaTi2O5 ferroelectric thick film was less than the thickness of the thick sol-filled viscous bonding layer, which may be due to the annealing treatment after the thick sol filling causing the ferroelectric film to be lossy.

[0068] The BaTi2O5 ferroelectric thick film prepared above was characterized, and the results are as follows:

[0069] Figure 4 This is the XRD diffraction pattern of BaTi2O5 ferroelectric thick film. It can be seen from the figure that the diffraction peak is obvious and basically coincides with the BaTi2O5 peak.

[0070] Figure 5 3 is a scanning electron microscope image of the BaTi2O5 ferroelectric thick film. It can be seen from the image that the surface of the BaTi2O5 ferroelectric thick film prepared in Example 1 is relatively dense.

[0071] Figure 6 3 is a scanning electron microscope image of the edge of the BaTi2O5 ferroelectric thick film. It can be seen from the figure that the edge of the BaTi2O5 ferroelectric thick film prepared in Example 1 is relatively thick, about 152μm.

[0072] Figure 7 3 is a piezoelectric force microscope hysteresis loop spectrum of the BaTi2O5 ferroelectric thick film. It can be seen from the figure that the BaTi2O5 ferroelectric thick film prepared by Example 1 can obtain a hysteresis loop, indicating that the BaTi2O5 ferroelectric thick film prepared by the present invention has more significant ferroelectric properties.

[0073] Embodiment 2:

[0074] A barium titanium-based ferroelectric thick film——BaTiO3 ferroelectric thick film

[0075] The preparation method thereof is different from that of Example 1 in that: in step (i), when preparing the composite precursor dilute gel and the composite precursor concentrated gel, Ba(CH3COO)2 (99.99%), C 16 H 36 O4Ti (≥97.00%) and CH3COOH (>99.50%) raw materials, weigh 5.11g of Ba(CH3COO)2, and the amount of other substances added varies accordingly. The remaining steps are the same as in Example 1.

[0076] The BaTi2O5 ferroelectric thick film prepared above was characterized, and the results are as follows:

[0077] Figure 8 This is the XRD diffraction pattern of BaTiO3 ferroelectric thick film. It can be seen from the figure that the diffraction peak is obvious and basically coincides with the BaTiO3 peak.

[0078] Fig. 9 3 is a scanning electron microscope image of the BaTiO3 ferroelectric thick film. It can be seen from the figure that the edge of the BaTiO3 ferroelectric thick film prepared in Example 2 is relatively thick, about 120 μm.

[0079] Fig.10 This is the piezoelectric force microscopy hysteresis loop spectrum of the BaTiO3 ferroelectric thick film prepared in Example 2. It can be seen from the figure that the BaTiO3 ferroelectric thick film prepared in Example 2 can obtain a hysteresis loop, indicating that the BaTiO3 ferroelectric thick film prepared by the present invention has more significant ferroelectric properties.

[0080] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a barium-titanium-based ferroelectric thick film, characterized in that: The method comprises the following steps: 1) preparing a barium precursor dilute solution and a barium precursor concentrated solution containing a barium source and a hydrolysis inhibitor, a titanium precursor dilute solution and a titanium precursor concentrated solution containing a titanium source and a hydrolysis inhibitor, mixing the barium precursor dilute solution and the titanium precursor dilute solution, adding an anti-cracking agent and aging to obtain a composite precursor dilute gel, mixing the barium precursor concentrated solution and the titanium precursor concentrated solution, adding an anti-cracking solvent and aging to obtain a composite precursor concentrated gel; 2) Spin coating the composite precursor dilute gel on the substrate for multiple times, and drying and heating after each spin coating to obtain a dilute sol three-dimensional network adhesion layer, and sintering it once to obtain a first-stage substrate; 3) Spin coating the thick gel on the first-stage substrate in step 2) for multiple times, and drying and heating after each spin coating to obtain a thick sol-filled viscous bonding layer, and sintering it twice to obtain a second-stage substrate; 4) Annealing the second stage substrate in step 3) to obtain a barium-titanium based ferroelectric thick film.

2. The method for preparing the barium-titanium-based ferroelectric thick film according to claim 1, characterized in that: In step 1), in the dilute barium precursor solution, the feed ratio of the barium source, the solvent and the hydrolysis inhibitor is (5-6) g: (20-30) mL: (6-8) mL, and in the concentrated barium precursor solution, the feed ratio of the barium source, the solvent and the hydrolysis inhibitor is (5-6) g: (18-24) mL: (6-8) mL; In the titanium precursor dilute solution, the feed ratio of the titanium source, the solvent and the hydrolysis inhibitor is (5-7) mL: (25-35) mL: (6-8) mL, and in the titanium precursor concentrated solution, the feed ratio of the titanium source, the solvent and the hydrolysis inhibitor is (5-7) mL: (20-28) mL: (6-8) mL; The volume ratio of the dilute barium precursor solution or the concentrated barium precursor solution to the anti-cracking agent is 1:(0.17-0.2); In the composite precursor dilute gel and composite precursor concentrated gel, the molar ratio of barium element to titanium element is 1:(1-2).

3. The method for preparing the barium-titanium-based ferroelectric thick film according to claim 2, characterized in that: The preparation method of the dilute barium precursor solution or the concentrated barium precursor solution is as follows: a barium source and a solvent are mixed, stirred once and stirred twice, and then a hydrolysis inhibitor is added to obtain the dilute barium precursor solution or the concentrated barium precursor solution; During the first stirring, the stirring temperature is 55-65°C, and during the second stirring, the stirring temperature is 75-85°C.

4. The method for preparing the barium-titanium-based ferroelectric thick film according to claim 2, characterized in that: The barium source is Ba(CH3COO)2, and the titanium source is C 16 H 36 O4Ti, the solvent is CH3COOH.

5. The method for preparing the barium-titanium-based ferroelectric thick film according to claim 1, characterized in that: In step 1), the hydrolysis inhibitor is selected from any one of ethylene glycol monoethyl ether, ethylenediaminetetraacetic acid or citric acid; the anti-cracking agent is selected from any one of acetylacetone, ethylene carbonate or polyol; during the stirring, the stirring temperature is 75-85°C; during the aging, the aging temperature is 26-30°C, and the aging time is 24-36h.

6. The method for preparing the barium-titanium-based ferroelectric thick film according to claim 1, characterized in that: In step 2), the substrate is a platinum substrate or an aluminum substrate; in the spin coating of the composite precursor dilute gel, the number of spin coatings is 5-6 times, the spin coating speed is 4000-5000RPM, and the spin coating time is 30s; in the drying treatment, the drying temperature is 110-130°C, the drying time is 2-4min, and the drying atmosphere is air or oxygen; in the heating treatment, the heating temperature is 380-410°C, the heating time is 1-2min, and the heating atmosphere is air or oxygen; in the primary sintering, the sintering temperature is 790-810°C, the sintering time is 55-70min, and the sintering atmosphere is air or oxygen.

7. The method for preparing the barium-titanium-based ferroelectric thick film according to claim 1, characterized in that: In step 3), in the spin coating of the thick gel, the number of spin coating is 5-6 times, the spin coating speed is 4000-5000RPM, and the spin coating time is 30s; in the drying treatment, the drying temperature is 110-130°C, the drying time is 2-4min, and the drying atmosphere is air or oxygen; in the heating treatment, the heating temperature is 380-410°C, the heating time is 1-2min, and the heating atmosphere is air or oxygen; in the secondary sintering, the sintering temperature is 790-810°C, the sintering time is 55-70min, and the sintering atmosphere is air or oxygen.

8. The method for preparing the barium-titanium-based ferroelectric thick film according to claim 1, characterized in that: In step 4), in the annealing treatment, the annealing temperature is 950-1100° C., the annealing time is 290-310 min, and the annealing atmosphere is air or oxygen.

9. The method for preparing the barium-titanium-based ferroelectric thick film according to claim 1, characterized in that: In step 2), the thickness of the dilute sol three-dimensional network adhesion layer is 100-200 μm; in step 3), the thickness of the thick sol-filled viscous adhesion layer is 200-300 μm; in step 4), the thickness of the barium-titanium-based ferroelectric thick film is 150-250 μm.

10. A barium-titanium-based ferroelectric thick film, characterized in that: It is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of sodium bismuth titanate-based ferroelectric film

    CN101805181A

  • Preparation method of BaTi2O5 thin films growing in a preferred orientation

    CN102584335A

  • Preparation method of flexible epitaxial ferroelectric film

    CN107256866A

  • Preparation method of strontium titanate film with adjustable heat conductivity coefficient

    CN114907116A

  • Bismuth strontium titanate-based lead-free relaxor ferroelectric film, preparation method and application

    CN115368131A